CD99 isoforms regulate CD1a expression in human monocyte‐derived DCs through ATF‐2/CREB‐1 phosphorylation. Issue 6 (6th May 2016) - Mahiddine, Karim; Mallavialle, Aude; Bziouech, Hanen; Larbret, Frédéric; Bernard, Alain; Bernard, Ghislaine
Abstract : The short form of CD99 is obtained by alternative splicing of long form transcript; an inclusion of an 18‐bp cassette introduces an in‐frame stop codon, generating CD99 SF as a truncated protein product. Both CD99 forms express the same extracellular and transmembrane regions while they differ in their cytoplasmic regions. Interestingly, the alternatively spliced isoforms of CD99 transcripts are differentially expressed in a cell type‐specific manner. Here we show that CD99 isoforms expression is modified during human dendritic cells differentiation and that CD99 is involved in regulation of CD1a expression. Abstract : CD1a expression is considered one of the major characteristics qualifying in vitro human dendritic cells (DCs) during their generation process. Here, we report that CD1A transcription is regulated by a mechanism involving the long and short isoforms of CD99. Using a lentiviral construct encoding for a CD99 short hairpin RNA, we were able to inhibit CD99 expression in human primary DCs. In such cells, CD1a membrane expression increased and CD1A transcripts were much higher in abundance compared to cells expressing CD99 long form (CD99LF). We also show that CD1A transcription is accompanied by a switch in expression from CD99LF to expression at comparable levels of both CD99 isoforms during immature DCs generation in vitro. We demonstrate that CD99LF maintains a lower level of CD1A transcription by up‐regulating the phosphorylated form of the ATF‐2 transcription factor and that CD99 short form (SF) is required to counteract this regulatory mechanism. Elucidation of the molecular mechanisms related to CD99 alternative splicing will be very helpful to better understand the transcriptional regulatory mechanism of CD1a molecules during DCs differentiation and its involvement in the immune response.